P09.14 The role of IDO1 and cellular senescence in the efficacy of PD-1 pathway blockade and radiotherapy in aged mice with glioblastoma. (21st September 2022) - Asimakidou, E; Bell, A; Bommi, P; Wainwright, D
Abstract : Background: Glioblastoma is the most common primary brain tumor in adults with a median overall survival between twelve to fifteen months. 1, 2 The prognosis is worse for patients older than 65 years of age. 3 Aging is associated with senescence, which leads to secretion of proinflammatory cytokines and increased levels of the immunosuppressive enzyme indoleamine-2, 3-dioxygenase 1 (IDO1). 4 Increased levels of IDO1 at an advanced age may attenuate the efficacy of immunotherapy. Materials and Methods: One hundred and seven mice between 79 and 92 weeks of age with differential Ido1 expression were intracranially injected with syngeneic murine GL261 cells and treated with PD-1 monoclonal antibodies and radiotherapy. The mice have been monitored for ninety days. U87 glioblastoma cells were cultured and treated with interferon-γ and NU223612 . Results: PD-1 blockade and irradiation were less effective when Ido1 expression was preserved. Mouse lines with Ido1 knockout in dendritic and endothelial cells had better survival. There was a higher senescent cell burden within the brain tumor than the extra-tumoral tissue in mice reaching the humane endpoint. In U87 glioblastoma cells, interferon-γ induced upregulation of PD-L1 and IDO1 in a similar pattern. IDO1 degradation resulted in concomitantly lower levels of PD-L1. Conclusions: Taken together, these results suggest that the treatment protocol with PD-1 pathway blockade plus radiotherapy should be combined with IDO1 inhibitors and potentially with senolytics to achieve a better therapeutic outcome in the elderly population with glioblastoma. References: Wen PY, Kesari S. Malignant gliomas in adults. New England Journal of Medicine 2008 Jul 31;359 (5):492–507. Delgado-López PD, Corrales-García EM. Survival in glioblastoma: a review on the impact of treatment modalities. Clinical and Translational Oncology 2016 Nov;18 (11):1062–71. Ladomersky E, Scholtens DM, Kocherginsky M, et al . The coincidence between increasing age, immunosuppression, and the incidence of patients with glioblastoma. Frontiers in pharmacology 2019 Mar 27;10 :200. Ladomersky E, Zhai L, Lauing KL, et al . Advanced Age Increases Immunosuppression in the Brain and Decreases Immunotherapeutic Efficacy in Subjects with Glioblastoma. Clin Cancer Res 2020 Oct 1;26 (19):5232–5245. Disclosure Information: E. Asimakidou: None. A. Bell: None. P. Bommi: None. D. Wainwright: None.